Embracing the digital economy: Exploring the role of trust, perceived ease of use, and religiosity on intention to use Islamic peer-to-peer lending - Alrasyid, Harun; Rabbani, Mustafa Raza; Afifudin, Afifudin (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
This study investigates the pivotal roles of trust, perceived ease of use, and religiosity on individuals' intentions to adopt Islamic peer-to-peer (P2P) lending platforms within the digital economy context. The novelty of this study lies in its focus on an area that has received limited attention in prior studies (Islamic P2P lending) and the inclusion of individual factors, particularly religiosity, in the analysis. Additionally, a five-point Likert scale survey and purposive sampling technique were employed, targeting young Muslim potential borrowers aged 18-24 (Generation Z) who are presently engaged in microbusiness activities and have knowledge of financial technology. However, they had not yet utilized any P2P lending platforms. Data from three hundred twenty-three respondents was analyzed to investigate the relationships between variables. The results of this study suggest that all examined variables, including trust, perceived ease of use, and religiosity, have a significant and positive impact on individuals' willingness to use Islamic P2P lending. This implies that the more trust individuals have in Islamic P2P lending platforms, the easier they perceive them to use, and the stronger their religious beliefs, the more likely they are to accept and utilize these new Islamic financial services.